2016
DOI: 10.1080/1120009x.2016.1201272
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Blue-Carba test: reduction in the detection time of carbapenemases performed from a 4-hour bacterial lawn

Abstract: The increase in carbapenem-resistant gram-negative bacteria is a matter of concern due to the limited therapeutic options available. In severe infections caused by these isolates, the rapid detection of the mechanisms of resistance is vital. We described a slightly modified version of the Blue-Carba test, rapid Blue-Carba test, which allows the detection of carbapenemases at 4 h of incubation from a haze of bacterial growth obtained from a positive blood culture. It was able to detect carbapenemase-producing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The BCT proved to be fast (detection observed ≤2 hours), highly sensitive, specific with accuracy up to 95.8%, and very cheap. These findings are in agreement with previous reports (9,10,14). The percentages of agreement between the BCT and multiplex PCR for carbapenemase genes methods for each species were comparatively good, the lowest one recorded for, 86.28%, and the highest for 95.15% as mentioned before emphasizing that BCT was able to characterize the CPE in a simple, rapidly and accessible way, and it can be implemented in clinical laboratories and hospitals with the advantage of having the affordability, accuracy and mainly speed to obtain results when compared traditional methods and molecular techniques for the detection of carbapenemase genes are costly, slow and are limited by the targets included (18).…”
Section: Discussionsupporting
confidence: 94%
“…The BCT proved to be fast (detection observed ≤2 hours), highly sensitive, specific with accuracy up to 95.8%, and very cheap. These findings are in agreement with previous reports (9,10,14). The percentages of agreement between the BCT and multiplex PCR for carbapenemase genes methods for each species were comparatively good, the lowest one recorded for, 86.28%, and the highest for 95.15% as mentioned before emphasizing that BCT was able to characterize the CPE in a simple, rapidly and accessible way, and it can be implemented in clinical laboratories and hospitals with the advantage of having the affordability, accuracy and mainly speed to obtain results when compared traditional methods and molecular techniques for the detection of carbapenemase genes are costly, slow and are limited by the targets included (18).…”
Section: Discussionsupporting
confidence: 94%
“…The plates were incubated at 37°C for 2 hours and carbapenemase activity was determined when test and negative control solution were respectively, yellow versus blue, yellow versus green and green versus blue. Non CPs failed to change color of indicator and both solution remained either blue or green[ 16 18 ]. Blue carba test was done in duplicate on the promising CPs isolates after plasmid extraction.…”
Section: Methodsmentioning
confidence: 99%
“…An interesting finding was the decreased diagnostic sensitivity for the detection of VIM activity in anaerobic versus aerobic bottles (53.6% and 100%, respectively), raising the hypothesis that this enzyme may be downregulated, inactivated, or rapidly degraded in anaerobic bottles. Previous studies have shown high sensitivity values when metallo-␤-lactamases are detected directly from BCs by colorimetric methods (8)(9)(10)(11), immunochromatographic tests (14,16), or MALDI-TOF-based hydrolysis assays (17,18), even though these screening were performed only on spiked aerobic BC bottles. More recently, Cointe et al have reported the low reproducibility of the RESIST-4 O.K.N.V.…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of genotypic diagnostic methods for the detection of ␤-lactamase-encoding genes in blood cultures (BCs) are currently available, they are expensive procedures requiring skilled personnel and are not able to identify all ESBL-or carbapenemase-encoding genes (6). Thus, during the last decade, several phenotype-based assays have been developed to detect ESBL or carbapenemase production in BCs, including colorimetric methods (7)(8)(9)(10)(11)(12)(13), immunochromatogenic assays (14)(15)(16), and ␤-lactam hydrolysis assays combined with matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) (17)(18)(19)(20).…”
mentioning
confidence: 99%